Atomic Layer Deposition of 2D Metal Dichalcogenides for Electronics, Catalysis, Energy Storage, and Beyond. Issue 6 (18th January 2021) - Mattinen, Miika; Leskelä, Markku; Ritala, Mikko
Abstract: 2D transition metal dichalcogenides (TMDCs) are among the most exciting materials of today. Their layered crystal structures result in unique and useful electronic, optical, catalytic, and quantum properties. To realize the technological potential of TMDCs, methods depositing uniform films of controlled thickness at low temperatures in a highly controllable, scalable, and repeatable manner are needed. Atomic layer deposition (ALD) is a chemical gas‐phase thin film deposition method capable of meeting these challenges. In this review, the applications evaluated for ALD TMDCs are systematically examined, including electronics and optoelectonics, electrocatalysis and photocatalysis, energy storage, lubrication, plasmonics, solar cells, and photonics. This review focuses on understanding the interplay between ALD precursors and deposition conditions, the resulting film characteristics such as thickness, crystallinity, and morphology, and ultimately device performance. Through rational choice of precursors and conditions, ALD is observed to exhibit potential to meet the varying requirements of widely different applications. Beyond the current state of ALD TMDCs, the future prospects, opportunities, and challenges in different applications are discussed. The authors hope that the review aids in bringing together experts in the fields of ALD, TMDCs, and various applications to eventually realize industrial applications of ALD TMDCs. Abstract : Atomic layer deposition is one of the most promising methods for producing 2D transition metal dichalcogenides for various applications from electronics to catalysis, energy storage, and beyond. In this review, the potential and challenges of atomic layer deposition for these applications are systematically evaluated and compared to each other as well as to other deposition methods.